Role of lamp type in conventional batch and micro-photoreactor for photocatalytic hydrogen production - Meinhardová, Vendula; Dubnová, Lada; Drobná, Helena; Matějová, Lenka; Kočí, Kamila; Čapek, Libor (Frontiers in Chemistry, 2023)
The use of an irradiation source with a homogeneous distribution of irradiation in the volume of the reaction mixture belongs to the essential aspects of heterogeneous photocatalysis. First, the efficacy of six lamps with various radiation intensity and distribution characteristics is contrasted. The topic of discussion is the photocatalytic hydrogen production from a methanol-water solution in the presence of a NiO-TiO2 photocatalyst. The second section is focused on the potential of a micro-photoreactor system–the batch reactor with a micro-reactor with a circulating reaction mixture, in which the photocatalytic reaction takes place using TiO2 immobilized on borosilicate glass. Continuous photocatalytic hydrogen generation from a methanol-water solution is possible in a micro-photoreactor. This system produced 333.7 ± 21.1 µmol H2 (252.8 ± 16.0 mmol.m−2, the hydrogen formation per thin film area) in a reproducible manner during 168 h.